2015
DOI: 10.1007/s13593-015-0296-z
|View full text |Cite
|
Sign up to set email alerts
|

Control of NO3 − and N2O emissions in agroecosystems: A review

Abstract: Energized electron flows through biological systems sustain nature's complexity. They drive bacterial, archaeal, and fungal oxidation-reduction processes and enable to introduce CO 2 and N 2 from the atmospheric pool. Electron flux-based food webs convert soil organic matter (SOM) in virgin forest and permafrost soils, over-fertilized agricultural land, grassland systems, compost/wastewater treatment plants, oceans, rain forests, savannahs, and forests of the temperate climate zones, and have their strategy ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 113 publications
(160 reference statements)
0
11
0
Order By: Relevance
“…Both nitrate and ammonium are the major N forms available in soils for plants (Andrews et al., 2013; Tegeder and Masclaux-Daubresse, 2017). In both natural and agricultural soils, microbial processes in soils favor a mixed nutrition with fluctuating contents of the respective sources depending on the environmental conditions of temperature and soil water content and the type of fertilizers applied, among other factors (Benckiser et al., 2015). In addition, when both inorganic-N sources are available in plants, ammonium is preferentially taken up and assimilated into organic molecules due to its more chemically reduced status than nitrate, thus saving metabolic energy during its assimilation (Andrews et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both nitrate and ammonium are the major N forms available in soils for plants (Andrews et al., 2013; Tegeder and Masclaux-Daubresse, 2017). In both natural and agricultural soils, microbial processes in soils favor a mixed nutrition with fluctuating contents of the respective sources depending on the environmental conditions of temperature and soil water content and the type of fertilizers applied, among other factors (Benckiser et al., 2015). In addition, when both inorganic-N sources are available in plants, ammonium is preferentially taken up and assimilated into organic molecules due to its more chemically reduced status than nitrate, thus saving metabolic energy during its assimilation (Andrews et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…DMPP did not inhibit urea hydrolysis in this study. DMPP only affects ammonia‐oxidizing bacteria (AOB) in soil 30–33 . Several previous studies have found that nitrification inhibitors rarely affect the hydrolysis of urea 16, 34 …”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the high nitrification potential in Che amplifying the inhibitory effect. Additionally, DMPP has a stronger inhibitory effect on AOB than AOA 13, 30, 31, 33 . Boric acid addition (UB) exhibited a significant inhibition effect on nitrification at an early stage of incubation and the inhibition efficiency decreased following incubation progress in both soils.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the highest fluxes to date have been measured in irrigated and fertilized systems [48,49]. N 2 O emissions from cultivated soils result from the biological nitrification and denitrification processes [50]. Thus, the understanding of the soil and environmental factors regulating the microbial populations is necessary to choose appropriate N 2 O mitigation strategies.…”
Section: Nitrification and Denitrificationmentioning
confidence: 99%